Well-being & social provision of children of overseas Filipino workers in Poblacion, Nueva Valencia, Guimaras. - Ganancial, Zenny G.
Forty-one (41) children of Overseas Filipino Workers from Poblacion, Nueva Valencia, Guimaras, participated in this study. Their age ranges from 12-17 years old and at their high school level. Respondents' fathers were mostly away and majority of them were working as seafarer. OFW Children's wellness was at good level despite of one or both of their parents were working abroad. Children were adequately provided with social support of people around them.